2019
DOI: 10.1039/c8cc09614g
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion in high pressure layered perovskite Ca2GeO4

Abstract: We report the high pressure synthesis of a layered perovskite Ca 2 GeO 4 which is found to have the Ruddlesden-Popper structure with I4 1 /acd symmetry. Consonant with our recent predictions [Ablitt et al., npj Comput. Mater., 2017, 3, 44], the phase displays pronounced uniaxial negative thermal expansion over a large temperature range. Negative thermal expansion that persists over a large temperature range is very unusual in the perovskite structure, and its occurrence in this instance can be understood to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…n = 1, phases in Figure 1). Certain compounds of RP1 (Ca 2 MnO 4 , 18,19 Sr 2 RhO 4 , 20,21 Sr 2 IrO 4 22 and Ca 2 GeO 4 23 ) and RP2 (Ca 3 Mn 2 O 7 24 ) oxides exhibit uniaxial NTE (along their layering axis only) over a particularly wide temperature range, often exceeding 1000 K.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…n = 1, phases in Figure 1). Certain compounds of RP1 (Ca 2 MnO 4 , 18,19 Sr 2 RhO 4 , 20,21 Sr 2 IrO 4 22 and Ca 2 GeO 4 23 ) and RP2 (Ca 3 Mn 2 O 7 24 ) oxides exhibit uniaxial NTE (along their layering axis only) over a particularly wide temperature range, often exceeding 1000 K.…”
mentioning
confidence: 99%
“…In this study we have maximised NTE by selecting a Ruddlesden-Popper system with the lowest layer thickness, n = 1 (which had previously been shown to be optimal for compliance 33 ) and then tuning tolerance factor to the low-t edge of NTE phase stability window, where the CLTE is most negative. We were thus able to synthesise a compound with a CLTE of -8.1 ppm/K at 125 K, which represents record low-temperature uniaxial NTE in a RP rotation phase (compared to -7.6 ppm/K in Ca 2 GeO 4 at 150 K 23 ). We also demonstrated that by changing composition, the CLTE may be tuned smoothly through to positive values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The a lattice parameter shows a monotonic decrease on cooling but the c parameter (interplanar spacing) first decreases on cooling to 100 K, followed by a steady increase on further cooling. No low-temperature measurements on other Ba 3 Ln(BO 3 ) 3 polymorphs have been reported, but similar behaviour has been observed in the layered compound α-SrCr 2 O 4 and in Ruddlesden-Popper oxides; in both cases this is associated with distortions of the layers [20,37]. Rietveld refinements at each temperature showed no significant changes in the Tb atomic positions across the range 12-300 K, indicating that the magnetic layers retain their 2D triangular geometry, but there was a steady decrease in the zposition of the Ba1 site by 4 % on cooling from 300 K to 12 K (see Supplementary Information, Fig.…”
Section: Crystal Structurementioning
confidence: 73%
“… 5 Recent work on hybrid-improper Ruddlesden–Popper phases 11 , 12 has shown that nonpolar distortions such as octahedral rotations often give relatively small energy gains (compared with polar cation displacements in proper systems) and that different rotation modes can have similar energy gains. This gives a fairly shallow energy landscape with competing ground states and hence the potential to switch between phases giving more complex behavior such as antiferroelectricity, 12 negative thermal expansion, 13 , 14 and relaxor behavior. 15 This provides a powerful motivation to understand the competition between different mechanisms/distortions and the consequences for structure and properties.…”
Section: Introductionmentioning
confidence: 99%